ChemInform Abstract: One‐Pot Multistep Synthesis of Trisubstituted Alkenes from N‐Tosylhydrazones and Alcohols. Issue 10 (March 2015) - Sha, Qiang; Wei, Yunyang
Abstract Tosylhydrazones derived from aliphatic aldehydes or ketones, such as cyclohexanone or butyraldehyde, do not afford the desired trisubstituted alkenes.